New Developments in Geotechnical Earthquake Engineering. (7th July 2014) - Changwei, Yang; Tianbao, Su; Jianjing, Zhang; Lin, Du
Abstract : Based on the review on the advances of several important problems in geotechnical seismic engineering, the authors propose the initial analysis theory of time-frequency-amplitude (known as TFA for short), in an effort to realize the organic combination of time and frequency information and develop a groundbreaking concept to the traditional idea in the geotechnical seismic engineering area.